Stranger things and Dungeons & dragons : the rise of Hellfire - Houser, Jody; Campbell, Eric (Writer) (Dark Horse Books, 2025)
"Spell slinging, sword swinging, and the luck of the dice have shaped the lives of the Stranger Things boys well before they had real monsters to face. This D&D Crossover features Eddie Munson's Rise to defacto leader of the Hellfire Club, his recruitment of Lucas, Dustin, and Mike, and glimpses into the fantasy worlds they conquered together"-- Provided by publisher.